Modelling intermittence and river fl ow in the semi-arid region of Brazil: The Umbuzeiro River, Ceará - Domingos Lima, Gabriela (Revista Ciência Agronômica, 2021)
Research shows an increase in the intermittence of rivers of different spatial scales. Exploring intermittence in semi-arid regions, also characterised by a scarcity of data, is important for understanding the process on a global scale. The aim of this study, therefore, was to evaluate the ability of a physically based hydrological model (WASA) to simulate simultaneously the intermittence and fl ow of the Umbuzeiro River, whose basin is located in Aiuaba, Ceará. The analysis was carried out in three nested basins: the Benguê Reservoir (933 km2 ), the Aroeira Reservoir (800 km2 ) and the Aiuaba Experimental Basin (AEB, 12 km2 ). Eleven simulations were carried out, altering various parameters (saturated hydraulic conductivity of the soil on the slopes and on the riverbed, hydraulic conductivity of the crystalline basement, depth of the riverbed, and the rainfall intensity parameter of the model). The model better represented the larger basins (10³ km2 ) compared to the smaller scale basin (10¹ km2 ). The simulations showed a marked improvement once the hydraulic conductivity of the soils as measured in situ had been applied, confi rming the physical basis of the model. The most sensitive parameter for the generation of fl ow was the saturated hydraulic conductivity of the soil. This can be explained by the prevalence of Hortonian fl ow in the basin. It was concluded that none of the parameterisations was successful in simultaneously representing the two processes (intermittence and fl ow) on the scales of the three basins.